Relationships of Basal Level of Serum 17-Hydroxyprogesterone with that of Serum Androstenedione and Their Stimulated Responses to a Low Dose of ACTH in Young Adult Patients with Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency - Kang, Min Jae; Kim, Shin Mi; Lee, Young Ah; Shin, Choong Ho; Yang, Sei Won (Journal of Korean medical science, 2011)
A single measurement of serum 17α-hydroxyprogesterone (17OHP) level can be unreliable because of its marked diurnal variation. We investigated the relationship of serum level of 17OHP with that of androstenedione (AD), which shows a smaller diurnal variation. And we tested whether the responses of these two hormones to low-dose ACTH stimulation are correlated in patients with 21-hydroxylase deficiency. Baseline serum 17OHP and AD levels were measured in 87 patients and a low-dose ACTH stimulation test was performed in 41 patients. The basal 17OHP level correlated positively with the basal AD level independently of sex, type of 21-hydroxylase deficiency, and the time of day of blood sampling (n = 87, R(2) = 0.75, P < 0.001). The area under the curve of 17OHP and AD correlated positively with their respective basal levels. The fold-change increase in 17OHP after ACTH injection correlated negatively with the basal 17OHP level, but that of AD did not correlate with the basal AD level. The random serum 17OHP level, used in the clinic, is a reliable guide and a low-dose ACTH stimulation test provides no extra benefit for assessing the treatment adequacy in patients with 21-hydroxylase deficiency.